(untitled) (Prudentia Iuris, 2017)
The latest technological developments are even more requiring a paradigm shift and a change in our worldview, together with a new reflection about our position in the cosmos. One of the most evident consequences of the recent technological developments is the current “ecological question”, and with it the rise of some philosophies that are trying to rethink the cosmological and metaphysical question as well. Deep ecology wants, in fact, to respond precisely to the current questions generated by the development of new technologies, through a worldview that very often lies in the ontology of processes (as in the case of transpersonal ecology), which is also the theoretical basis of posthumanism. Within the theoretical framework of these paradigms, it is not possible to raise the question of human dignity, since the limits that define human beings are not recognized. We argue that it will be possible to take into account human dignity only starting from a human ecology, which recognizes human dependence as a condition of possibility of the human person’s value.